Plan de negocios para la creación la microempresa “servicios de logística y trámites de pagos” - Loja S., John A. (2009)
SERVIFASTER Cía. Ltda., “Logistic and Payment Transactions Services” will be a micro enterprise that provide services such as services payments and packet sends to people that work at far away zones of urban perimeter or someone that can not realize their self, because work in office time (8:00 to 17:00) or rotary times, do not have own mobilization, do not have access to on line payment or have less knowledge about this. In order to attend the unsatisfied necessities of this people group, we have considered proposing the next services: • Payments of Basic and Private Services. • Sending of documents and/or little packets to 25kg. For begging, our market will be the industrial sectors that are localize out of the Guayaquil and Duran Cities. 1° Sector, North of Guayaquil and Vía Durán Tambo. 2° Sector, Vía a Daule and Prosperina. 3° Sector, Perimetral and Vía a la Costa. The office will be located in the Av. Juan Tanca Marengo around Km 2.5, because this zone is much better for our company logistic activities.